Uranium Recovery from Phosphates for Self-Sufficient Nuclear Power in the Eastern Mediterranean - Nassar H. S. Haidar (Science and Technology of Nuclear Installations)
Production of phosphate fertilizers (PF), without uranium recovery, amounts to dispersing uranium compounds on agricultural fields. These compounds are naturally hidden in phosphate rock deposits prior to processing. Such a dispersion is a cumulative environmental damage, that may become rather catastrophic in few hundred years, under the current rates & impurities of phosphate fertilization of agricultural lands. It is also an avoidable irreversible waste of one of the world’s major energy resources. This study demonstrates quantitatively the low impact of U costs on the nuclear power generation costs, which happens, so far, to be a main reason for nonrecovery of uranium from the present PF industry. It reports on novel procedures for (i) estimating the required U feed to nuclear power plants (NPPs), (ii) pricing U as a function of its cumulative world production, and (iii) for quantifying U accumulation in phosphate fertilized lands. We also demonstrate that countries of the eastern Mediterranean can, in the long run, become collectively U partially self-sufficient, by recovering U from their phosphate resources, to power 13.2% of their entire electric energy generation contemporary needs.